2006
DOI: 10.4049/jimmunol.176.6.3391
|View full text |Cite
|
Sign up to set email alerts
|

The BZLF1 Homolog of an Epstein-Barr-Related γ-Herpesvirus Is a Frequent Target of the CTL Response in Persistently Infected Rhesus Macaques

Abstract: Although CD8+ T lymphocytes targeting lytic infection proteins dominate the immune response to acute and persistent EBV infection, their role in immune control of EBV replication is not known. Rhesus lymphocryptovirus (rhLCV) is a γ-herpesvirus closely related to EBV, which establishes persistent infection in rhesus macaques. In this study, we investigated cellular immune responses to the rhLCV BZLF1 (rhBZLF1) homolog in a cohort of rhLCV-seropositive rhesus macaques. rhBZLF1-specific IFN-γ ELISPOT responses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Using the IFN-g ELISPOT, CMV-reactive T-cells were detected at approximate frequencies in the range of &500-3000 SFC/10 6 PBMC (1/2000 to 1/300, respectively), and LCV-reactive T-cell frequencies in the range of &50-500 SFC/10 6 PBMC (1/20 000 to 1/2000, respectively). The frequencies we detect are similar to those reported in rhesus macaques for CMV (Ambagala et al, 2011;Kaur et al, 2002;Pitcher et al, 2002) and LCV (Fogg et al, 2005(Fogg et al, , 2006, as well as those reported in humans for CMV and EBV (Hislop et al, 2007;Tan et al, 1999;Waldrop et al, 1997), indicating that cynomolgus macaques are similar to rhesus macaques and humans with regards to the size of the memory T-cell pool specific for CMV and LCV.…”
Section: Discussionsupporting
confidence: 74%
“…Using the IFN-g ELISPOT, CMV-reactive T-cells were detected at approximate frequencies in the range of &500-3000 SFC/10 6 PBMC (1/2000 to 1/300, respectively), and LCV-reactive T-cell frequencies in the range of &50-500 SFC/10 6 PBMC (1/20 000 to 1/2000, respectively). The frequencies we detect are similar to those reported in rhesus macaques for CMV (Ambagala et al, 2011;Kaur et al, 2002;Pitcher et al, 2002) and LCV (Fogg et al, 2005(Fogg et al, , 2006, as well as those reported in humans for CMV and EBV (Hislop et al, 2007;Tan et al, 1999;Waldrop et al, 1997), indicating that cynomolgus macaques are similar to rhesus macaques and humans with regards to the size of the memory T-cell pool specific for CMV and LCV.…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, the potentially oncogenic EBNA2, EB-NALP, EBNA3, EBNA3C, and LMP1 latency III transformation program may have not evolved without LMP1 induction of IFNmediated innate and adoptive immune responses (24). This latter hypothesis can be tested by infection of Rhesus macaques with Rhesus EBV, which has been reverse-genetically modified so as to express a dominant-negative inhibitor of LMP1 mediated IRF7 activation (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, cell-mediated and humoral immune responses against rhLCV have been reported in macaques; however, their protective value remains unexplored in this in vivo system (Fogg et al, 2005;Fogg et al, 2006;Orlova et al, 2011a;Orlova et al, 2011b). The difficulty in manipulating the macaque immune system to interrogate the functional relevance of rhLCVspecific immune responses points to the limitation of this in vivo system.…”
Section: Lymphocryptoviruses In Monkeysmentioning
confidence: 99%